Peran Komite Sekolah dalam Meningkatkan Mutu Pendidikan - Wina Nabilla Ramadhanti; Mimin Maryati (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2022)
Since the implementation of decentralization of education, maximizing the role of school and community stakeholders has become very important in supporting the success of the education process in schools. The aspects that are seen are the role of the school committee as a giver of considerations, supporters, controllers, and roles as mediators. The purpose of this study is to find out how important the role of the school committee in improving the quality of education is. This study uses a descriptive method with a qualitative approach with the subject of research on the role of school committees in improving the quality of education at Wirautama Patrol Junior High School. The results of this study show that Wirautama Junior High School can provide an example to other schools that Wirautama Patrol Junior High School has good cooperation with the school committee so that schools can have good quality education. The school committee supports all programs implemented by the school, so that the quality of education at the Wirautama Patrol Junior High School can run well, because it has good relations with the committee and has support from the community.